Pulp and paper production from oil palm empty fruit bunches: a current direction in Malaysia - Mohd Ali, Maimunah; Muhadi, Nur ‘Atirah; Hashim, Norhashila; Abdullah, Ahmad Fikri; Mahadi, Muhammad Razif (Sixscientia Resources, 2020)
The pulp and paper industry is advanced rapidly since there are many types of raw materials containing cellulose fibres that could be used to produce different kinds of paper by different methods in the mills. In Malaysia, one of the abundant non-wood materials for pulp and paper production is empty fruit bunch (EFB) from the oil palm. The EFB is the main fibrous residue and natural fibre which has promising potential as an alternative to replace woody materials. This study provides insight into the use of EFB as an alternative non-wood fibre resource in pulp and paper making. The potential of oil palm EFB transformed into valuable fibre material was elaborated. In this review, detailed information on the properties of EFB for pulp and paper making process to identify the chemical composition and fibre morphology were discussed. Recent advanced applications including nanocellulose from EFB, polymeric hydrogel, and antimicrobial papers were discussed to demonstrate high commercialization for pulp and paper technology. The three-dimensional (3D) printing technique has been employed due to the high complexity of paper products. The future trends and challenges regarding the use of EFB in pulp and paper making were also reviewed. This study demonstrated that the EFB has met the demand of the market chains as a potential raw material in paper making and manufacturing.